Marketing Performance of MSME 4.0 Amidst COVID-19 Transition: Marketing Mix, E-CRM and Risk Perception - Miguna Astuti; Rosali Sembiring (LPPM Universitas Terbuka, 2024)
Purpose – This study was conducted to analyze the influence of marketing mix strategy on performance through E-CRM and risk perception of COVID-19. Methodology – The study used a quantitative approach and the processed data was obtained from 302 MSME actors who have operated digitally for over three years in Indonesia. Furthermore, the data analysis was carried out using the Path Analysis. Findings – The results showed that marketing mix strategy could influence performance, independently or through E-CRM and Risk Perception of COVID-19. Meanwhile, Electronic-Customer Relationship Management (E-CRM) showed a strong influence on marketing performance. Even though mix strategy could influence an increase in performance, the impact showed a higher rate with E-CRM activities and consideration towards risk perception of the pandemic. Originality – This analysis was important because of the low study related to marketing performance in Indonesian MSME 4.0. Furthermore, this was the first study to investigate the effect of marketing mix strategy, E-CRM, and risk perception of the pandemic on performance in one model.